2003
DOI: 10.1007/s00122-003-1307-z
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for resistance to powdery mildew in pepper under natural and artificial infections

Abstract: Epidemics of powdery mildew due to Leveillula taurica is an increasing problem in pepper production areas, particularly in coastal regions or greenhouse cultivation. The highly resistant genitor 'H3' was submitted to genetic analysis and QTL mapping in order to promote the introgression of its oligogenic resistance into large and sweet-fruited cultivars. The doubled-haploid progeny from the cross 'H3' (resistant) by 'Vania' (susceptible) was tested for resistance under both natural field infection and artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Most QTL studies in pepper have focused on commercial traits, such as fruit and production traits (Rao et al, 2003;Zygier et al, 2005;Barchi et al, 2009;Lee et al, 2011;Alimi et al, 2013) as well as studies related to identification of QTL associated with resistance to diseases (Lefebvre et al, 2003;Mimura et al, 2009;Kim et al, 2011). A limited number of studies have identified QTL associated with vegetative parts of the plant (leaves, stem internodes, and petioles) (Barchi et al, M.M.…”
Section: Introductionmentioning
confidence: 99%
“…Most QTL studies in pepper have focused on commercial traits, such as fruit and production traits (Rao et al, 2003;Zygier et al, 2005;Barchi et al, 2009;Lee et al, 2011;Alimi et al, 2013) as well as studies related to identification of QTL associated with resistance to diseases (Lefebvre et al, 2003;Mimura et al, 2009;Kim et al, 2011). A limited number of studies have identified QTL associated with vegetative parts of the plant (leaves, stem internodes, and petioles) (Barchi et al, M.M.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inheritance of these traits has been extensively studied and the quantitative trait loci (QTLs) that contribute to disease resistance and fruit traits have been reported (Ben Chaim et al, 2001a, 2001bLefebvre et al, 2003;Minamiyama et al, 2005Minamiyama et al, , 2007Popovsky and Paran, 2000;Thabuis et al, 2003;Voorrips et al, 2004). In addition to the above-mentioned traits, axillary shooting, flowering date, primary axis length, and number of leaves are also important for pepper production.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous QTL and genic studies have identified multiple loci involved in the expression of a single trait (Calborg and Haley 2004). In addition, interval mapping and composite interval mapping have been used successfully to identify QTL associated with specific phenotypes that led to the identification of statistically significant interactions (Shook and Johnson 1999;Lefebvre et al 2003;Ma et al 2006). However, in all these cases, additional studies were required to ascertain the actual genetic model defining the interaction of the various loci.…”
Section: Discussionmentioning
confidence: 99%